Comparison of radiocesium and stable isotope ratios of carbon and nitrogen among three stocks of Pacific cod (Gadus macrocephalus) around Hokkaido, Japan. (February 2018) - Nakamura, Tsugiya; Tanaka, Toshiyasu; Kimura, Osamu; Fujii, Yukiko; Haraguchi, Koichi; Endo, Tetsuya
Abstract: Hokkaido, the northernmost of the main islands of Japan, is surrounded by the North Pacific Ocean, the Japan Sea and the Okhotsk Sea, and three independent stocks of Pacific cod are thought to inhabit those three areas. The Fukushima Dai-ichi Nuclear Power Plant (FDNPP), which is located in the north of Honshu, the main island of Japan, was disputed in 2011. Most of the radiocesium from the FDNPP was released into the western North Pacific Ocean, and the biota in those areas were considerably contaminated soon after the FDNPP accident. We analyzed radiocesium in Pacific cod caught around Hokkaido between 2011 and 2015. The radiocesium was predominantly detected in the cod caught in the North Pacific Ocean, and not in those caught the Japan Sea and the Okhotsk Sea. These results suggest that the cod caught in the Pacific Ocean around Hokkaido moved through the contaminated area off the FDNPP. Highlights: The Fukushima Dai-ichi Nuclear Power Plant (FDNPP) in Japan was disputed in 2011. North Pacific Ocean around DDNPP was contaminated with radiocesium. Hokkaido is surrounded by the North Pacific Ocean, the Japan Sea and the Okhotsk Sea, Radiocesium was detected only in the cod caught in the Pacific Ocean of Hokkaido. The cod caught in Hokkaido may move through the contaminated area off the FDNPP.